Perioperative Safety in Plastic Surgery: Is the World Health Organization Checklist Useful in a Broad Practice?. Issue 5 (May 2016) - Biskup, Nataliya; Workman, Adrienne D.; Kutzner, Emily; Adetayo, Oluwaseun A.; Gupta, Subhas C.
Abstract : Introduction: In October 2007, the World Health Organization (WHO) introduced the Safe Surgery Saves Lives Program, the cornerstone of which was a 19-item safe-surgery checklist (SSC), in 8 selected hospitals around the world. After implementation, death rates decreased significantly from 1.5% to 0.8% ( P = 0.003), inpatient complications reduced from 11% to 7% ( P < 0.001), as did rates of surgical site infection ( P < 0.001) and wrong-sided surgery ( P < 0.47), across all sites. On the basis of these impressive reductions in complications and mortality, our institution adopted the WHO SSC in April 2009, with a few additional measures included, such as assuring presence of appropriate implants and administration of preoperative antibiotics and thromboembolic prophylaxis. Our purpose was to evaluate the efficacy and applicability of the surgical safety checklist in a multisurgeon plastic surgery hospital-based practice, by analyzing its effect on morbidity and outcomes. Methods: A retrospective review of the morbidity and mortality data from the Department of Plastic Surgery at Loma Linda University Medical Center was conducted from January 2006 to July 2012. Data on morbidity and mortality before and after implementation of the surgical safety checklist were analyzed. Results: The most common complications were wound related, including infection, seroma and/or hematoma, dehiscence, and flap-related complications. No significant decrease in the measured complications, neither total nor each specific complication, occurred after the implementation of the SSC. Although verifying appropriate administration of antibiotic, presence of appropriate equipment and materials, performing a preoperative formal pause, and verifying the execution of the other measures included in the SSC is critical, untoward outcomes after implementation of the checklist did not measurably decrease. In its current form as this time, the checklist does not seem to be efficacious in Plastic Surgery. Conclusions: Although certain elements of the WHO SSC checklist are universal and should be adopted, certain specific aspects require modification to improve applicability in a plastic surgery–specific practice. This necessitates the creation of a surgical safety checklist specifically for plastic surgery as other surgical specialties have proposed.